2008
DOI: 10.3354/meps07436
|View full text |Cite
|
Sign up to set email alerts
|

Archipelago-wide coral recovery patterns since 1998 in the Chagos Archipelago, central Indian Ocean

Abstract: Patterns of coral recovery are analysed across reefs of the Chagos Archipelago, which spans 400 × 250 km in the central Indian Ocean. This archipelago mostly lacks direct human impacts and is subject only to global changes such as a rise in sea surface temperature. Following very heavy coral mortality (mostly > 90%) caused by the 1998 warming event, and despite 2 further sub-lethal bleaching events, the recovery of coral cover, colony numbers and juvenile recruitment has been good in many parts of the archipel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 20 publications
8
99
1
Order By: Relevance
“…Recovery post-1998 occurred within about 10-12 yr (Pisapia et al 2016), a trend replicated at other remote Indian Ocean sites (e.g. Chagos; Sheppard et al 2008). In other areas of the Indian Ocean, recovery trajectories post-1998 were more divergent, with some reefs recovering successfully and others undergoing phase shifts to states with lower coral cover and diminished carbonate budgets (Graham et al 2015).…”
Section: Introductionmentioning
confidence: 82%
“…Recovery post-1998 occurred within about 10-12 yr (Pisapia et al 2016), a trend replicated at other remote Indian Ocean sites (e.g. Chagos; Sheppard et al 2008). In other areas of the Indian Ocean, recovery trajectories post-1998 were more divergent, with some reefs recovering successfully and others undergoing phase shifts to states with lower coral cover and diminished carbonate budgets (Graham et al 2015).…”
Section: Introductionmentioning
confidence: 82%
“…Of these factors, SST is not likely to have been markedly different to that on reefs in adjacent areas with low human population where much better coral cover and fish populations remain. It is being repeatedly shown that even where warming is causing reef deterioration, recovery can be rapid where there are minimal direct impacts, and that recovery may not occur at all where there is also pollution and overfishing Sheppard et al, 2008;Hagan et al, 2008). In the Grand Récif, it is more likely that the rapid rise of discharged, untreated sewage from the growing city is very important, along with the rapid rise in human population with its associated artisanal fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of coral populations of the Indian and Pacific Ocean have described the 1998 post-bleaching coral recovery as a result of life history traits and recruitment dynamics (Arthur et al 2006, Golbuu et al 2007, Sheppard et al 2008. Montastraea annularis is a species with low recruitment rates (Hughes and Jackson 1985, Szmant et al 1997, Hughes and Tanner 2000, Edmunds and Elahi 2007.…”
Section: Discussionmentioning
confidence: 99%